P81 DISARRAY AND REMODELING OF THE RADIAL ARTERY IN WOMEN WITH SPONTANEOUS CORONARY ARTERY DISSECTION: THE FUCHSIA STUDY - Rosa Maria Bruno; Nicole Di Lascio; Abtehale Al Hussaini; Daniela Guarino; Saverio Vitali; Piercarlo Rossi; Davide Caramella; Bernardo Cortese; Francesco Faita; Stefano Taddei; Lorenzo Ghiadoni; David Adlam (Artery Research, 2017)
Background: Spontaneous coronary dissection (SCAD) may represent a manifestation of fibromuscular dysplasia (FMD); thus, preclinical lesions might be found in extracoronary vessels with similar size and wall ultrastructure, such as the radial artery. Methods: Two 5′-clips from the left radial artery were obtained by Vevo MD (70 MHz probe, FUJIFILM, VisualSonics). Radial wall showed two echogenic interfaces: the 1st (lumen-media) and the 2nd (media-adventitia). Intima-media (IMT), adventitia (AT), and global thickness (IMAT) and wall cross-sectional area (WCSA) Measured. Vascular wall disarray was assessed calculating the root mean square error (RMSE) between 20 gray-level profiles crossing the two interfaces and the profile obtained averaging them, normalized for the maximum value of the corresponding mean profile (RMSE/mean).